PERAN LABORATORIUM PENDIDIKAN FISIKA UNIVERSITAS MUHAMMADIYAH METRO DALAM PENYELENGGARAAN PENELITIAN - Anisa, Latifatu; Suseno, Nyoto; Salim, M. Barkah (Universitas Muhammadiyah Metro, 2022)
Abstract: Pure experimental research in the UM Metro Physics Education study program is very minimal, therefore the role of the Physics Education Laboratory is needed in helping students or lecturers.The goal of this study to exsplore the role and constraints of the Laboratory of Physics Education of Muhammadiyah University of Metro for conducting research. This is a qualitative descriptive research, using interview, observation and questionnaire method. The sources of data are laboratory users, laboratory managers, and laboratory assistants. The analysis of data using qualitative by doing source triangulation and method triangulation. The result found that (1) Laboratory of Physic Education was 78% with good role playing categorie, its role is to provide laboratory facilities, measuring instruments and tools and materials.(2) Constraints faced are in physical facilities 23.68% with little constraint. The recomendation of this reseach,(1) Laboratory of Physic Education of Muhammadiyah University Of Metro to improve laboratory facilities even better. (2) Researchers can use Laboratory of Physic Education of Muhammadiyah University Of Metro to conduct research. (3) Schools can make laboratory of physics education of Muhammadiyah University Of Metro as models of research laboratories in schools.Keywords: The role, physics education laboratory